Cervical cancer screening utilization among healthcare professionals in Ethiopia: systematic review and meta-analysis - Tizazu, Michael Amera; Demsash, Addisalem Workie; Mamo, Tadesse; Kebede, Tirusew Nigussie; Mihretie, Abebe; Mamo Negash, Kassa; Amogne, Fetene Kassahun; Wubetu, Abate Dargie (Frontiers in Global Women's Health, 2025)
BackgroundCancer of the cervix is the second most common cancer among women worldwide, with about over 660 000 new cases and approximately ninety-four percent of the 350 000 cervical cancer-related death happened in low- and middle-income countries. Effective screening initiatives are particularly crucial in preventing cervical cancer in women. Therefore, the purpose of this systematic literature review was to investigate the pooled prevalence of Ethiopian female healthcare professionals' cervical cancer screening utilization.MethodsPublished articles were searched from different major international databases (PubMed, Cochrane Library, Scopus, Web of Science, Since Direct, Google Scholar). Direct Google searches were used for additional sources mainly for gray and preprint studies. This review included studies that reported either the use of cervical cancer screening or cervical cancer screening predictors in Ethiopia. All published and unpublished studies through May/2024 and reported in the English language were retrieved to assess eligibility for inclusion in this review. The Newcastle-Ottawa Scale quality assessment tool was used to assess the quality of the included studies and Egger's test was used to assess the publication bias.ResultsIn order to calculate the pooled prevalence of cervical cancer screening, 2,919 female healthcare professionals participated in the review. Articles were published from 2015 to 2024. The pooled Utilization of cervical cancer screening in Ethiopia, as determined by a meta-analysis of ten articles was 13.59% (95% CI: 7.53, 19.65).Conclusion and recommendationThe estimated/pooled cervical cancer screening utilization was found to be lower than the World Health Organization recommendations as the estimator revealed in the meta-analysis. The low utilization of Cervical Cancer (CCa)screening practice despite they are healthcare professionals is a significant concern that can impact the broader efforts to combat cervical cancer. Based on the this reviews the authors recommend regular monitoring and evaluation of the CCa screening habits of healthcare professionals and the effectiveness of implemented interventions. It is necessary to explore the factors that enable or hinder CCa screening and address the issue through qualitative or mixed-method studies.